Густав Вільгельмович Нейгауз – музикант, педагог, просвітитель: етапи творчого шляху - Долгіх, М. (Студії мистецтвознавчі, 2008)
For the first time amongst all Ukrainian issues they show the facts of creative and vital way of teacher, performer, researcherdesigner, father of prominent pianist-teacher of XX century Genrih Neuhaus. The role of Gustav Neuhaus is marked as a founder of piano performer school of Elisavetgrad region.